2020
DOI: 10.1038/s41598-020-72931-6
|View full text |Cite|
|
Sign up to set email alerts
|

Epifluorescence-based three-dimensional traction force microscopy

Abstract: We introduce a novel method to compute three-dimensional (3D) displacements and both in-plane and out-of-plane tractions on nominally planar transparent materials using standard epifluorescence microscopy. Despite the importance of out-of-plane components to fully understanding cell behavior, epifluorescence images are generally not used for 3D traction force microscopy (TFM) experiments due to limitations in spatial resolution and measuring out-of-plane motion. To extend an epifluorescence-based technique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Traction forces generated by cells lead to matrix deformation, enabling force transmission to distant cells. In a 3D scenario, traction forces generated by a single cell or spheroid can be well determined by traction force microscopy, which measures the displacement of microbeads evenly distributed in the matrix (36,37). We observed that collagen fibers were aligned between two SK-MEL-5 cells.…”
Section: Discussionmentioning
confidence: 93%
“…Traction forces generated by cells lead to matrix deformation, enabling force transmission to distant cells. In a 3D scenario, traction forces generated by a single cell or spheroid can be well determined by traction force microscopy, which measures the displacement of microbeads evenly distributed in the matrix (36,37). We observed that collagen fibers were aligned between two SK-MEL-5 cells.…”
Section: Discussionmentioning
confidence: 93%
“…Traction forces generated by cells lead to matrix deformation, enabling force transmission to distant cells. In a 3D scenario, traction forces generated by a single cell or spheroid can be well determined by traction force microscopy, which measures the displacement of microbeads evenly distributed in the matrix [28,29]. We observed that collagen fibers were aligned between two SK-MEL-5 cells.…”
Section: Discussionmentioning
confidence: 93%
“…Traction forces generated by cells lead to matrix deformation, enabling force transmission to distant cells. In a 3D scenario, traction forces generated by a single cell or spheroid can be well determined by traction force microscopy, which measures the displacement of microbeads evenly distributed in the matrix [21,22]. For cell-cell distant mechanical communication, where two distantly located cells simultaneously apply forces on matrix mesh network, the displacement of the beads per se might not be suitable to reflect the forces applied as in the case for tug-of-war.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to digital image/volume correlation (DIC/DVC) and particle image velocimetry (PIV), which are subset-correlation-based techniques (see a summary of various full-field tracking methods in Table 2). The increased specificity of the tracked particles can be beneficial to applications such as quantitative biological motion tracking [4,5,6,7,8,9] and fluid mechanics for flow measurements [10,2,11,12]. However, it remains a challenge to uniquely and robustly match particles throughout an image sequence.…”
Section: Motivation and Significancementioning
confidence: 99%